Health Surveillance of Wild Brown Trout (Salmo trutta fario) in the Czech Republic Revealed a Coexistence of Proliferative Kidney Disease and Piscine Orthoreovirus-3 Infection - Pojezdal, Ľubomír; Adamek, Mikolaj; Syrová, Eva; Steinhagen, Dieter; Minářová, Hana; Papežíková, Ivana; Seidlová, Veronika; Reschová, Stanislava; Palíková, Miroslava (Pathogens (Basel, Switzerland), 2020)
The population of brown trout (Salmo trutta fario) in continental Europe is on the decline, with infectious diseases confirmed as one of the causative factors. However, no data on the epizootiological situation of wild fish in the Czech Republic are currently available. In this study, brown trout (n = 260) from eight rivers were examined for the presence of viral and parasitical pathogens. Salmonid alphavirus-2, infectious pancreatic necrosis virus, piscine novirhabdovirus (VHSV) and salmonid novirhabdovirus (IHNV) were not detected using PCR. Cell culturing showed no viruses as well, and serological analysis of 110 sera did not detect any specific antibodies against VHSV or IHNV. Fish from two rivers were positive for the presence of piscine orthoreovirus-3 (PRV-3), subtype PRV-3b. However, none of the PRV-3-positive fish showed gross pathologies typically associated with PRV infections. By far the most widespread pathogen was Tetracapsuloides bryosalmonae which was confirmed in each of the examined locations, with a prevalence of up to 65% and 100%, as established by immunohistochemistry and PCR, respectively. Furthermore, up to 43.8% of fish showed signs of proliferative kidney disease caused by T. bryosalmonae, suggesting that this parasite is a main health challenge for brown trout in the Czech Republic.
Keywords: serology; Tetracapsuloides bryosalmonae; viral hemorrhagic septicemia; PCR; infectious pancreatic necrosis; salmonid alphavirus; infectious hematopoietic necrosis; immunohistochemistry